Is Cronbach's alpha sufficient for assessing the reliability of the OSCE for an internal medicine course?. (December 2015) - Al-Osail, Aisha; Al-Sheikh, Mona; Al-Osail, Emad; Al-Ghamdi, Mohannad; Al-Hawas, Abdulaziz; Al-Bahussain, Abdullah; Al-Dajani, Ahmed
Abstract Background The number of medical students accepted into medical programs is increasing, which has made the traditional long/short case style of examination difficult to conduct. At Dammam University, the program is shifting to the use of the Objective Structural Clinical Examination (OSCE), which may solve some of these difficulties, including issues with reliability, validity index and exam duration. Results A pilot study was conducted over one semester. A total of 207 examinees in three groups took the OSCE and written exams. The OSCE consisted of 18 clinical stations and required 3–4.3 h/day. The written exam contained 80 multiple-choice questions. The Cronbach's alpha for each group was 0.7, 0.8, and 0.9. Correlations for all stations ranged from 0.7 to 0.8, which indicated good stability and internal consistency with minor differences in the progression of the indexes. The reliability of the written exam was 0.79, and the validity of the OSCE was 0.63, as assessed using Pearson's correlation. Conclusion No single reliability index can be considered a perfect assessment tool to solve this issue. Thus, at least two to three indexes should be used to ensure the reliability of the OSCE.